THU0139 Depressive symptoms and vitamin d in patients with early arthritis. (15th June 2017) - Freier, D; Biersack, M; Detert, J; Burmester, G-R; Uebelhack, R; Braun, T; Hoehne-Zimmer, V
Abstract : Background: There is a high prevalence of depression in patients with rheumatic disorders. Especially, in rheumatoid arthritis, it is one of the most prevalent co-morbidities with 16% to 38%. Vitamin D (VD) deficiency is one of the known risk factors for depressive disorders. On the other hand, a VD deficiency has often been detected in rheumatic diseases. A possible correlation between these two co-morbidities has not been investigated so far in patients with early arthritis (EA). Objectives: The aim of this study was to examine the association between VD deficiency and depression and/or anxiety disorders in patients who have presented themselves for the first time in the EA clinic. Methods: Patients with a suspected EA (at least one swollen joint without previous trauma or joint infection with a symptom duration of 6 weeks to 12 months) received a screening date within five work days. The VD status (25-hydroxy-VD3 ) was obtained during the first EA clinic consultation. In addition, each patient completed questionnaires on the disease history, as well as evaluated self-assessment questionnaires including the health assessment questionnaire (HAQ) and the Hospital Anxiety and Depression Scale (HADS). The hereby-obtained results of disease activity, VD-status and HADS-scores were investigated. In the observation period from June 2012 to March 2015, 75 patients fulfilled the inclusion criteria of completed results and questionnaires as well as a disease duration of less than 12 months. Results: The mean age of this EA cohort was 51.7±16.9 years (♀ 65.3%, mean disease duration: 4.0±3.0 months). The prevalence of VD deficiency (<75 nmol/l) was 73.3%. 48.0% of EA patients showed a positive global distress score (≥13). The mean HADS global distress score in VD sufficient patients was 10.2±8.6 vs 13.3±6.9 in deficient patients. The observed difference was not statistically significant. There was neither an association between gender, age and VD status nor was there any difference in the laboratory parameters (e.g. C-reactive protein, rheumatic factor, anti citrullinated peptide, hemoglobine) or assessment of functional status (e.g. HAQ, disease activity score by 28 joints). Conclusions: The prevalence of VD deficiency is higher in EA patients with 73% than in the general German population (vs. 60%). The prevalence of positive distress with 50% is also higher. Interestingly, no association of deficient VD levels and positive distress in the HADS was detected in our examined EA cohort. This might be explained by the early stage of disease, but further studies are necessary to evaluate this new insight. References: Dougados, M., et al., Prevalence of comorbidities in rheumatoid arthritis and evaluation of their monitoring: results of an international, cross-sectional study (COMORA). Ann Rheum Dis, 2014. 73(1): p. 62–8. Linseisen J, Bechthold A, Bischoff-Ferrari HA et al. Vitamin D und Prävention ausgewählter chronischer Krankheiten – Stellungnahme. In: V. DGfEe, ed. Bonn 2011. Merlino LA, Curtis J, Mikuls TR, Cerhan JR, Criswell LA, Saag KG, et al. Vitamin D intake is inversely associated with rheumatoid arthritis: results from the Iowa Women's Health Study. Arthritis Rheum. 2004;50(1):72–7. Disclosure of Interest: None declared